Analisis Kinerja Keuangan PT Bank Rakyat Indonesia (Persero) Tbk Menggunakan Pendekatan Rasio Keuangan Periode 2020–2024 - Ananda Ratu Ayesha; Dalizanolo Hulu (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study uses financial ratios, common size, and comparative analysis to examine PT Bank Rakyat Indonesia (Persero) Tbk's financial performance from 2020 to 2024. The study uses secondary data from annual financial reports and a descriptive quantitative methodology. According to the findings, the COVID-19 pandemic put the corporation under financial strain in 2020, but it recovered significantly in 2021–2024. PT Bank Rakyat Indonesia (Persero) Tbk's overall financial performance is steady and shows excellent profitability, liquidity, solvency, and risk management.